Improving bandwidth efficiency in E-band communication systems - Mehrpouyan, Hani; Khanzadi, M. Reza; Matthaiou, Michail; Sayeed, Akbar M.; Schober, Robert; Hua, Yingbo (IEEE Communications Magazine, 2014)
The allocation of a large amount of bandwidth by regulating bodies in the 70/80 GHz band, that is, the E-band, has opened up new potentials and challenges for providing affordable and reliable gigabit-per-second wireless point-to-point links. This article first reviews the available bandwidth and licensing regulations in the E-band. Subsequently, different propagation models (e.g., the ITU-R and Cane models) are compared against measurement results, and it is concluded that to meet specific availability requirements, E-band wireless systems may need to be designed with larger fade margins compared to microwave systems. A similar comparison is carried out between measurements and models for oscillator phase noise. It is confirmed that phase noise characteristics, which are neglected by the models used for narrowband systems, need to be taken into account for the wideband systems deployed in the E-band. Next, a new MIMO transceiver design, termed continuous aperture phased (CAP)-MIMO, is presented. Simulations show that CAP-MIMO enables E-band systems to achieve fiber-optic-like throughputs. Finally, it is argued that full-duplex relaying can be used to greatly enhance the coverage of E-band systems without sacrificing throughput, thus facilitating their application in establishing the backhaul of heterogeneous Networks.<br
Keywords: Phase noise; MIMO; Wireless communicationtten; Attenuation; Bandwidth allocation; Transceivers